Strategic HR: Success Key to Organizational Effectiveness - Bhojanna, U.; Srikanth, I. G.; Tiwari, Abhishek (Prabandhan: Indian Journal of Management, 2013)
The management concept with a resource-based view among organizations is based on the critical importance of the human resource element, gaining competitive advantage through positioning itself as a strategic and an integral part responsible for attaining a paradigm shift in the field of organizational effectiveness. Astonishingly, the human resource management field has accepted a number of suggestions for the new role of manpower in organizations for strategic purposes, but it is lacking in its formulation and execution. This raises a question - where should human resource management focus upon (the superior executor role) to build human resource as strategic human resource? Through this paper, we wished to analyze the strategic issues concerned, and attempted to find how the answer to the aforesaid question can be appropriately given, and also aimed to analyze the degree of organizational effectiveness and organizational competency achieved through the evolved concept of strategic human resource management (SHRM).